12 - ANALYSIS OF PUBLIC INSTALLATION FOR SPORTS AND LEISURE THE CITY OF VILA VELHA – ES (Fiep Bulletin - online, 2011)
This study is characterized by a field survey of qualitative and quantitative, which sought to assess the conservation status and analyze data on the public spaces for sport and leisure in the city of Vila Velha-ES. The results point to a relationship inhabitants / unfavorable spaces, and the Administrative Region V, responsible for more inequality found (46,539 inhabitants and only 1 installation), while Region II has the highest rate of attendance (79,617 and 41 public spaces). The aim of this study is to present the results to the municipal government to alert them to the reform and expansion of existing spaces and the construction of new ones.
Keywords: public administration; public sports and recreation; local administration of sports